Interrupting Cow and the horse of a different color - Yolen, Jane (Yolen, Jane. Interrupting Cow (Series), 2022)
"There's a new horse at the farm, and he's unlike any of the others. That's because he's a zebra! Zebra knows a lot of jokes ... and he knows there's a big, bright world beyond the farm. He might just lead Interrupting Cow to her next big adventure!"--Page 2 of cover